Dynamic Soil Characterization and Site Response Estimation for Erbaa, Tokat (Turkey) - Akin, Muge K.; Kramer, Steven L.; Topal, Tamer (Springer, 2016)
Site amplification is one of the most important factors controlling damage in urban areas through strong earthquakes. Local site effects play an important role in earthquake-resistant design and should be considered for site response analyses. In this study, ground response analyses in Erbaa, Turkey, a settlement in the North Anatolian Fault Zone, using one-dimensional equivalent linear analysis and empirical approaches based on shear wave velocity profiles are evaluated and compared. The ground response analyses were performed with consideration of shear wave velocity, and modulus reduction and damping behavior for different confining pressure and plasticity index-dependent models. The results of ground response analyses and amplification values from empirical equations using shear wave velocity are illustrated in terms of amplification and predominant period maps of the seismically active Erbaa settlement area. The comparison has been made in these produced maps of the study area in order to evaluate different site response analyses.
Keywords: Ground Response Analysis; Soil Amplification; Erbaa; Turkey; Site Effect; Map